SABERES DOCENTES NA FORMAÇÃO INICIAL: O PLANEJARE O FAZER NO CONTEXTO DE UMA OFICINA DE FÍSICA. - AMANDA CRISTINA NAUJORKS (2025)
This research aimed to investigate the mobilization of teaching knowledge by pre-service teachers, seeking to identify how this knowledge is applied during the planning and implementation of a Physics workshop for high school students at a public school in Campo Grande-MS, Brazil. The research problem was: “What teaching knowledge is mobilized by pre-service teachers during the planning and implementation of a Physics workshop for high school students?” The study adopted a qualitative approach with an exploratory design. Data were collected through semi-structured interviews and lesson plans developed by the pre-service teachers and analyzed using Bardin’s (2021) Content Analysis. The research findings highlight the importance of rethinking initial teacher education to provide more meaningful experiences that prepare future educators for the challenges of the teaching profession. The methodology of planning and implementing workshops proved to be a valuable experience for the pre-service teachers. However, the study also revealed that most participants did not demonstrate a deep mastery of Physics content and faced challenges in translating this knowledge into teaching practice. The analysis of the pre-service teachers’ lesson plans revealed considerable diversity: while some demonstrated strong command of teaching knowledge and created more comprehensive plans, others encountered difficulties in organizing activities and defining objectives. Furthermore, the study emphasizes the importance of initial teacher education programs incorporating active student participation in school environments from the early semesters of the course. By engaging in lesson planning and execution, pre-service teachers have the opportunity to construct and consolidate their knowledge more effectively as they are confronted with the demands and challenges of the school environment. The suggested changes for initial teacher education include fostering stronger integration between universities and schools so that experiential and professional knowledge is developed gradually throughout the training process, rather than being concentrated in the final years during internship courses. The study also recommends creating extension courses to provide more practical opportunities for pre-service teachers, enhancing their ability to mobilize teaching knowledge.